Anatomical Basis of Cranial Neurosurgery - Seeger, Wolfgang (Springer International Publishing, 2018)
This didactic book clearly and systematically describes the anatomical-surgical fundamentals of cranial neurosurgery, relating them to norm variants, imaging modalities and interdisciplinary aspects. All illustrations, hand drawn in ink by the first author, are simple and self-explanatory. The book reflects the first author's lifetime experience as an academic neurosurgeon and teacher, as well as the second author's theoretical and practical knowledge of neurosurgical subspecialties such as epilepsy surgery. In addition to its core audience in neurosurgery, it provides all connected disciplines, in particular neuroradiology, neurology, neuropathology, ENT surgery, maxillofacial surgery and eye surgery, with unique anatomical insights into the neurosurgeon's perspective.